ASPEK THAYYIB PADA MAKANAN BERBAHAN DAGING: STUDI KEAMANAN PANGAN DAGING SAPI GILING DI PENGGILINGAN DAGING DNH, KECAMATAN GAMPING, SLEMAN, YOGYAKARTA - Sari, Bekti Wulan; Ikawati, Retty (Jurnal Sains dan Teknologi Pangan, 2025)
The word thayyib in food is always combined with halal as halalan thoyibban. Hence, food which complies thayyib is interpreted as a good halal product, does not contain harm or disease. Food safety of grounded beef is an important aspect to be studied from thayyib side considering that meat milling is a place that is prone to and at risk of contamination by pathogenic microbes, especially meat is perishable food. The purpose of this study was to analyze the application of thayyib in DNH meat milling service, especially food safety aspect through formalin testing, examining Escherichia coli, Salmonella, Vibrio cholerae, and Total Plate Count (TPC) contamination, supported by field observations, then studied using literature. Results showed that all samples reacted negatively to the formalin, V. cholerae, and E. coli tests, TPC ranging from 500-19,000 CFU/g. Sample HD1 was positive for Salmonella. TPC value of <1 x 106 CFU/g on all samples were met requirements of SNI 3932:2008 for fresh meat, while the detection of Salmonella sp. indicated the presence of suspected biological contamination. Inadequate conditions were found from each observation of the building yard, the grinding area, equipment, and food handler that could support biological contamination. Based on microbiological tests and observations, the aspect of food safety as part of thayyib had not been optimally fulfilled. It is recommended to the owner of the DNH meat milling to pay attention to cleanliness of the entire grinding area and the personal hygiene of food handler.